2015
DOI: 10.1016/j.peptides.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of nociceptin/orphanin FQ receptor signaling reverses LPS-induced depressive-like behavior in mice

Abstract: Nociceptin/orphanin FQ is the natural ligand of a Gi-protein coupled receptor named NOP. This peptidergic system is involved in the regulation of mood states and inflammatory responses. The present study aimed to investigate the consequences of blocking NOP signaling in lipopolysaccharide (LPS)-induced sickness and depressive-like behaviors in mice. LPS 0.8mg/kg, ip, significantly induced sickness signs such as weight loss, decrease of water and food intake and depressive-like behavior in the tail suspension t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 41 publications
(49 reference statements)
1
24
0
Order By: Relevance
“…Converging evidence has been obtained in genetic studies as NOP(e/e) mice and rats displayed an antidepressant-like phenotype. 25 More recent studies investigating lipopolysaccharide-induced depression 46 and learned helplessness 47 in mice confirmed previous findings and further corroborated the antidepressant-like activity of NOP antagonists. Researchers at Eli Lilly discovered the potent and selective NOP receptor antagonist, LY2940094, 48 which displayed antidepressant-like behavioural effects in the forced-swimming test in mice, an effect absent in NOP(e/e) animals.…”
Section: Antidepressant Actionssupporting
confidence: 79%
“…Converging evidence has been obtained in genetic studies as NOP(e/e) mice and rats displayed an antidepressant-like phenotype. 25 More recent studies investigating lipopolysaccharide-induced depression 46 and learned helplessness 47 in mice confirmed previous findings and further corroborated the antidepressant-like activity of NOP antagonists. Researchers at Eli Lilly discovered the potent and selective NOP receptor antagonist, LY2940094, 48 which displayed antidepressant-like behavioural effects in the forced-swimming test in mice, an effect absent in NOP(e/e) animals.…”
Section: Antidepressant Actionssupporting
confidence: 79%
“…In fact, the actions of distinct NOP antagonists (i.e., [Nphe 1 ]N/OFQ(1-13)-NH 2 , UFP-101, SB-612111, J-113397, LY2940094) has been well established in behavioral despair tests (Gavioli and Calo' 2013;Post et al 2015). Moreover, it is worth highlighting the studies of Vitale et al (2009) andMedeiros et al (2015) which have demonstrated that the blockade of NOP receptors reversed depressive-like behaviors induced by chronic exposure to an unpredictable sequence of mild stressful stimuli in rats and by the transient inflammatory process elicited by a single administration of lipopolysaccharide in mice. Very recently, a study performed with LY2940094 provided the first clinical evidence for an antidepressant effect of a NOP antagonist in depressed patients (Post et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, NOP antagonists induce antidepressantlike effect in rodents subjected to the forced swim, tail suspension, and chronic mild stress assays, which were abrogated by previous administration of N/OFQ (Redrobe et al 2002;Gavioli et al 2003;Gavioli et al 2004;Vitale et al 2009). NOP antagonists also counteracted LPS-induced depressive-like behavior in mice (Medeiros et al 2015). Importantly, NOP receptor knockout mice and rats display an antidepressant-like phenotype in behavioral despair assays (Gavioli et al 2003;Rizzi et al 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Inflammatory agents such as LPS (lipopolysaccharide) has been used to simulate a range of brain diseases; depression ( Medeiros et al, 2015 ), schizophrenia ( Zhu et al, 2014a ), autism ( Kirsten et al, 2015 ), Parkinson’s disease ( Sharma and Nehru, 2015 ), Alzheimer’s disease ( El-Sayed and Bayan, 2015 ) in rodents. LPS is a major component of the cell wall of gram negative bacteria and a potent activator of the inflammatory response, particularly of microglia.…”
Section: Introductionmentioning
confidence: 99%